Fertility sparing surgery in epithelial ovarian cancer in Italy: perceptions, practice, and main issues. (3rd April 2018) - Bergamini, Alice; Petrone, Micaela; Rabaiotti, Emanuela; Pella, Francesca; Cioffi, Raffaella; Rossi, Elena Giulia; Di Mattei, Valentina; Candiani, Massimo; Mangili, Giorgia
Abstract: About 2.7% of patients epithelial ovarian cancers (EOC) are younger than 40 and present with stage I disease. For this subset of women, the issue of fertility sparing surgery (FSS) has become critical. The aim of this survey was to investigate the management of EOC patients desiring to preserve fertility in Italy. A questionnaire consisting of 30 items was developed to evaluate: patient-selection criteria, rate of FSS, patient's counseling- and pregnancy-timing, fertility preservation, obstetrics, and oncologic outcomes. One expert clinician for each of 50 major gynecologic oncology centers was invited to participate. Data were entered into a database and statistically analyzed. 74% of questionnaires were complete. The proportion of EOC patients treated with FSS was <10%, 10%–20% and >20% in 70.3%, 24.3% and 5.4% of cases, respectively. Age, fertility preservation desire, histotype, and stage were considered relevant to select patients for a conservative treatment for 64.8%, 72.9%, and 78.3% of responders, respectively. Only 17 centers (45.9%) resulted to have an assisted reproductive technique service and Obstetrics Department. Our survey highlights discrepancies among oncologists in the management of patients with early EOC undergoing FSS. More efforts should be made to define and broadcast the best management before and after surgery.